Intellectual property rights knowledge and awareness: Academic level empirical analysis and recommendations - Kristina Popova; Marina Nacka (Journal of Contemporary Economic and Business Issues, 2017)
Commitment to Intellectual Property Rights (IPR) is a segment of students' positive or negative behavior in the academic community. We define the negative behavior as students' commitment to plagiarism and copyright violation. The overall objective of this paper is to give a recommendation to the non-IPR institutions that potentially show similar results in the level of awareness of students and their behavior regarding their academic program and teaching activities. This follows an empirical testing and analysis of the relationship between knowledge and the level of IPR awareness, and their influence over students' behavior at a non-IPR committed Faculty. In this regard, the paper tests if students that have higher level of awareness and knowledge tend to demonstrate a positive behavior towards IPR more frequently. We use an online survey to collect data and construct scales to measure the level of awareness, knowledge and the type of behavior. Treating the constructed scales as categorical data, we apply log-linear analysis. Results showed that the higher the awareness level, the more frequent the positive behavior. On the other hand, the analysis of the knowledge of students does not provide clear findings; however, it is associated with the level of awareness. The negative behavior, as concluded from the sample, arises from the high cost of acquiring the basic studying material. Nevertheless, understanding students' knowledge, awareness and behavior towards IPR could assist Faculties to implement policies for decreasing students' negative behavior, promoting academic integrity and improving students' ethics.
Keywords: C12; D83; I29; 330; Intellectual Property Rights; awareness; students' behavior; IPR policy recommendation